Total synthesis of ent-pavettamine - Zimuwandeyi, Memory (Beilstein J Org Chem, 2021)
Pavettamine, a plant toxin first isolated from Pavetta harborii in 1995, was previously identified as a polyamine with C(2) symmetry and a 1,3-syn-diol moiety on a C(10) carbon backbone – one of very few substituted polyamines to be isolated from nature. Its absolute configuration was later established by our first reported total synthesis in 2010. Herein we report the first total synthesis of the enantiomer of pavettamine, ent-pavettamine. The symmetrical structure of the molecule allows for the synthesis of a common C(5) fragment that can be divergently transformed into two synthons for later convergent coupling to furnish the target carbon framework. Based on the success of the protocol we employed for the synthesis of the naturally occurring pavettamine, (S)-malic acid was again the starting material of choice for the synthesis of the two individual C(5) fragments, with strategic differences in terminal-group manipulation allowing for the synthesis of ent-pavettamine rather than pavettamine. Chain extension and stereoselective ketone reduction were achieved using the (R)-methyl p-tolyl sulfoxide chiral auxiliary to give the desired 1,3-syn-diol C(5) unit. A protecting-group strategy was also developed for the orthogonal protection of the alcohol and amine functional groups as they were unveiled. The functionalized C(5) fragments were coupled via reductive amination revealing the C(10) carbon backbone. Deprotection of the alcohol and amine functional groups successfully provided ent-pavettamine as a TFA salt.